Feather pecking in laying hens housed in free-range or furnished-cage systems on French farms. Issue 6 (2nd November 2019) - Coton, J.; Guinebretière, M.; Guesdon, V.; Chiron, G.; Mindus, C.; Laravoire, A.; Pauthier, G.; Balaine, L.; Descamps, M.; Bignon, L.; Huneau-Salaün, A.; Michel, V.
ABSTRACT: 1. Beak trimming is currently used in France to avoid the negative consequences of severe feather pecking (SFP). However, this practice is controversial in terms of animal welfare, and forbidden in some European countries. 2. This study aimed to assess the prevalence of SFP in French laying hen farms, to describe how farmers manage this behavioural disorder and to better understand the risk factors involved. 3. A study was carried out from April 2015 to June 2016. Visits were paid to 79 flocks kept in furnished cages (FC) and 80 flocks in a free-range (FR) system. All the hens had trimmed beaks and were genotypically brown. The information collected included feather cover, skin damage, beak condition, farm and poultry house characteristics, livestock performance and management. 4. The prevalence of SFP in FC flocks was estimated at 32.9% (IC = 95%, [22.5; 43.3]) and the prevalence of cannibalism as 2.5% (IC = 95%, [0.7; 8.8]) at 70 weeks of age. The prevalence of SFP in FR flocks was estimated to be 23.8% (IC = 95%, [14.5; 31.1]) and the prevalence of cannibalism was 8.8% (IC = 95%, [4.3; 17.0]) at 61 weeks of age. 5. In FC flocks, SFP was associated with the combination of genotype, type and length of perches, cage area per hen, type of lighting, number of hens per cage and farm location. In FR flocks, feather cover was associated with use of the outdoor run, lighting programme, genotype, farm location and date of house construction.